Theoretical Foundations of Using Non-Continuous Texts in Teaching Russian as a Foreign Language - Ruziboev, Azizbek; Azizova, Nasiba Bakhritdinovna (The Lingua Spectrum, 2026)
The article examines the theoretical foundations for integrating non-continuous texts into the process of teaching Russian as a Foreign Language (RFL). Existing approaches to the definition, classification, and didactic potential of non-continuous texts are analyzed. Their role in developing students’ communicative, sociocultural, and cognitive competencies is highlighted. Particular attention is paid to the differences between continuous and non-continuous texts, as well as to the principles of selecting and adapting visual materials according to learners’ language proficiency levels. The necessity of a balanced combination of continuous and non-continuous texts in the educational process is substantiated. The article is intended for RFL teachers, master’s students, and researchers in the field of educational information visualization.